(3cfR GdObGFbs - (3YHO Gddg Hf CMeO Hf eMehO GdfSaj, CHh GdHQcGJ, MGaX GdOjf,J (B710 (3g` s
(3ChdgG (B:s
(3cJGH GdWgGQI s
(3BNQgG (B:s
(3JeJ GdcJGH HYhf Gddg Gdedc GdhgGH hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg CLeYjf s
(3GdfSNI HgG MhGTs
(3HChdg agQSJ ddeNWhWs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B32s
Keywords: (3Gdabg GdMfajs